Why should we check the tubes in IVF patients with ovarian endometriosis before embryo transfer? a retrospective study - Caglar Yazicioglu; Aysen Yuceturk; Ozge Karaosmanoglu; Ilke Ozer Aslan; Nuri Peker; Yigit Cakiroglu; Bulent Tiras (BMC Pregnancy and Childbirth)
Abstract Background The endometrioma accompanying hydrosalpinx can affect the success rate of in vitro fertilization (IVF). We aimed to determine the incidence of hydrosalpinx in infertile patients with endometrioma and its effects on in vitro fertilization success. Methods In our retrospective study, we performed hysterosalpingography (HSG) on patients diagnosed with endometrioma through ultrasound evaluation. Then, we performed diagnostic laparoscopy on patients with suspected tubal pathology and/or hydrosalpinx after HSG assessment. Laparoscopic tubal occlusion was performed for patients with hydrosalpinx. Results HSG was performed on 760 patients diagnosed with ovarian endometriosis. After the assessment of HSG images, hydrosalpinx was detected in 184 of 760 patients (24.2%) and diagnostic laparoscopy was performed. Unilateral or bilateral hydrosalpinx were detected at 65 of 184 (35.3%) patients. Laparoscopy and proximal tubal occlusion were performed in these patients. Incidence of hydrosalpinx was found to be 8.5% in IVF patients with ovarian endometrioma. Conclusion Tubal patency screening may be considered for the patients with endometrioma before embryo transfer to prevent IVF failure due to hydrosalpinx.